Development of Android application-based digital literacy media to improve the reading ability of ADHD students - Khair, Abdul; Pahrurrozi, Murtadlo; Purbaningrum, Endang; Saputra, Ahmad Yudi (Jurnal Inovasi Teknologi Pendidikan, 2023)
This study aims to help kids with Attention Hyperactivity disorder (ADHD) in inclusive classrooms become better readers. The ADDIE model, which stands for Analysis, Design, Development, Implementation, and Evaluation, is used in this study's RD (Research and Development) research. The study was conducted between 11 February and 12 April 2023. Eight kids with ADHD from 4 primary school classes at UNESA 2 Labschool participated in this study. Of these, two were in class 3, two were in fourth grade, two were in fifth grade, and two were in sixth grade. Ways for gathering data via a questionnaire. It is claimed that the outcomes of enhancing students' reading abilities with digital literacy media built on Android applications are reliable, applicable, and efficient. This study used a questionnaire as the data collection tool to assess its validity, usefulness, and efficacy. The Aiken's V validation result for digital literacy media was 0.89, deemed legitimate and highly acceptable for usage by material specialists. Experts in the media estimate Aiken's V average to be 0.93. The average percentage result for Android application-based digital literacy media is 89%, making it extremely practical. 91% of the time, it works. Media promoting digital literacy is therefore deemed effective. It is legitimate, practical, and efficient to use Android applications-based digital literacy media to help ADHD pupils with their reading abilities in inclusive schools.